The AD detector array: a new tool for studying diffractive physics at the ALICE experiment - Calvo Villar, Ernesto (2015)
We present a new detector array proposal for the ALICE experiment at LHC. This new subdetector is composed of four stations of scintillator pads and its main goal is to extend our current rapidity coverage. Therefore, we would have more sensitivity to tag the rapidity gaps related to the diffractive processes. In particular, we show a study of the performance of this new subdetector and its impact in our ability to select diffractive events. Certainly, this new system will contribute to improve the ALICE capabilities in addressing several subjects on diffractive physics.